PENGARUH PERTIMBANGAN ETIS TERHADAP PERILAKU MAHASISWA AKUNTANSI UNTUK MELAKUKAN TINDAKAN WHISTLEBLOWING - Dewi Kusuma Wardani; Alexander Anak Agung Kalli Ngara (Melati Institute, 2022)
The study aims to find out ethical considerations on the behavior of accounting students to carry out whistleblowing actions. The population used in this study was accounting students of Universitas Sarjanawiyata Tamansiswa Yogyakarta with a total sample of 77 respondents of Universitas Sarjanawiyata Tamansiswa students class of 2018-2020. Sampling in this study used snowball sampling technique. The data were analyzed using the IBM SPSS Statistics 21 program. The results of this study show that ethical considerations have a positive effect on the behavior of accounting students to carry out whistleblowing actions.